A high-tonnage 840 kN disc-shaped suspension porcelain insulator, its preparation method and application
Patent Information
- Application Number
- CN202611313023.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]但是,对于840 kN高吨位盘形悬式瓷绝缘子,瓷件头部、钢帽、钢脚和胶合剂层之间的载荷传递关系较为复杂,易在头部过渡区域及胶装界面产生应力集中,在长期风振、覆冰和交变拉伸载荷作用下可能出现瓷体微裂纹或胶层脱粘
本发明采用双圆弧渐变壁厚圆柱头部,并使其与钢帽圆弧应力缓冲槽、钢脚球面承压结构及改性水泥胶合剂层相配合,形成较为平缓的载荷传递路径,能够分散瓷件头部和胶装界面的局部应力,降低瓷体开裂及胶层脱粘的风险,提高绝缘子在长期交变载荷下的机械可靠性。
Smart Images

Figure CN123017648A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ultra-high voltage power transmission and transformation insulation devices, and in particular to an 840 kN high-tonnage disc suspension porcelain insulator, its preparation method, and its application. Background Technology
[0002] With the development of ultra-high voltage AC / DC power transmission and long-distance transmission projects from new energy bases, the application of large-section, multi-split conductors in lines crossing rivers and valleys, with large elevation differences, heavy icing, and strong winds is increasing, placing higher demands on the mechanical load-bearing capacity, electrical performance, and long-term reliability of insulators. Traditional lower-tonnage disc suspension insulators usually require multiple strings connected in parallel, leading to an increase in the number of insulators and connecting hardware, and a corresponding increase in tower load, project cost, and maintenance workload.
[0003] Existing technologies have improved the load-bearing structure, anti-pollution structure, and manufacturing process of large-tonnage insulators. For example, invention patent CN 104992794 A discloses a technology to improve the bonding strength and resistance to electrolytic corrosion by sanding the porcelain head, using the concave-convex structure of the inner wall of the iron cap, and using the zinc sleeve of the steel foot; invention patent CN 113113193 A discloses a technology to increase the creepage distance and improve the self-cleaning performance by using a three-umbrella structure; invention patent CN 110845224 A discloses a technology to improve the strength and aging resistance of porcelain insulators through raw material processing, molding, drying, firing, and bonding processes.
[0004] However, for 840 kN high-tonnage disc suspension porcelain insulators, the load transfer relationship between the porcelain head, steel cap, steel foot, and adhesive layer is relatively complex. Stress concentration is prone to occur in the transition area of the head and the adhesive interface. Under long-term wind vibration, icing, and alternating tensile loads, microcracks in the porcelain body or debonding of the adhesive layer may occur. At the same time, high-alumina thick-walled porcelain parts are quite sensitive to the particle size of raw materials, molding, drying, and firing regimes. Improper control of preparation parameters can easily lead to internal defects and performance dispersion.
[0005] Furthermore, the polluted, humid, and salt spray environments in UHVDC lines easily cause surface flashover and electrolytic corrosion of the steel feet. The anti-fouling and anti-corrosion effects of existing umbrella skirts and single zinc ring structures still have room for improvement. Visual inspection and specified load testing alone are insufficient to detect internal defects in ceramic components and early fatigue damage at the adhesive interface. Therefore, it is necessary to conduct coordinated improvements to the load-bearing structure, ceramic material preparation, adhesive system, anti-fouling and anti-corrosion structure, and reliability testing methods. Summary of the Invention
[0006] In view of this, the present invention provides an 840 kN high-tonnage disc-type suspension porcelain insulator, its preparation method, and its application. Through the coordinated design of the high-alumina porcelain insulator body, load-bearing connection structure, adhesive system, anti-pollution and anti-corrosion structure, and preparation and testing processes, the present invention achieves high load-bearing capacity, fatigue resistance, pollution flashover resistance, and corrosion resistance in the 840 kN disc-type suspension porcelain insulator. It has the advantages of good manufacturing stability and high operational reliability, and is suitable for UHV AC / DC heavy-load transmission lines, showing promising engineering application prospects.
[0007] The first aspect of the present invention provides an 840 kN high-tonnage disc suspension porcelain insulator, comprising a high-alumina porcelain insulating body, a cast steel cap, a steel foot, and a modified cement adhesive layer for adhesively connecting the high-alumina porcelain insulating body to the cast steel cap and the steel foot respectively. The high-alumina porcelain insulating body includes a cylindrical head and a gradient three-umbrella skirt located below the cylindrical head. The cylindrical head is a hollow cylindrical head. The outer and inner sides of the cylindrical head are formed by two tangent and connected arcs to form a double arc gradual wall thickness transition structure. The cylindrical side wall thickness of the cylindrical head is 23 mm, the top thickness is 22 mm, and the glued surface of the cylindrical head is provided with an anti-slip sand layer with a height of 0.6 mm. The inner wall of the cast steel cap is provided with an arc-shaped stress buffer groove. The top of the steel foot is a spherical pressure-bearing structure, which is matched with the inner double arc transition structure of the cylindrical head through the modified cement adhesive layer. The steel foot is fitted with a double-layer sacrificial zinc ring anti-corrosion assembly in the middle. The outer diameters of the upper, middle, and lower umbrellas of the gradient three-umbrella skirt decrease progressively from top to bottom, and the self-cleaning tilt angle of the umbrella surface is 12°.
[0008] Preferably, the height of the cylindrical head is 105±4 mm, the outer diameter is 125±4 mm, and the diameter of the hollow hole in the cylindrical head is 79±5 mm; the outer double arc includes a first outer arc and a second outer arc that are tangentially connected, the radius of the first outer arc is 24~28 mm, and the radius of the second outer arc is 8~12 mm; the inner double arc includes a first inner arc and a second inner arc that are tangentially connected, the radius of the first inner arc is 10~14 mm, and the radius of the second inner arc is 6~9 mm.
[0009] Preferably, the radius of the arc stress buffer groove is 6-10 mm and the radial depth is 2-4 mm; the radius of the spherical bearing structure is 35-45 mm and the height of the spherical crown is 8-12 mm; the radial thickness of the modified cement adhesive layer on one side of the cast steel cap is 8-12 mm, the axial thickness of the modified cement adhesive layer on the side of the steel foot at the top of the spherical surface is 10-15 mm, and the coaxiality deviation of the cast steel cap, the high-alumina ceramic insulating body, and the steel foot is ≤0.8 mm.
[0010] Preferably, the dry-based raw materials of the high-alumina ceramic insulation body include, by weight: 92-95 parts α-high-purity alumina powder, 3-5 parts low-sodium quartz powder, 1.5-2.5 parts low-potassium sodium feldspar, and 0.3-0.8 parts composite mineralizer; the purity of the α-high-purity alumina powder is not less than 99.5%, and the particle size D of the raw material after sand milling is... 90 ≤5 μm; the composite mineralizer is composed of magnesium oxide and barium carbonate in a mass ratio of 1:1 to 2:1.
[0011] Preferably, the modified cementitious binder, based on 100 parts by weight of high-alumina silicate cement, comprises 0.8 parts of polycarboxylate superplasticizer, 1.2 parts of artificial ceramic sand aggregate, and 0.5 parts of organic defoamer, with a water-cement ratio of 0.28 to 0.32, and the particle size of the artificial ceramic sand aggregate is 0.15 to 0.60 mm; the aluminate content of the high-alumina silicate cement is 35% to 50%.
[0012] Preferably, the structural height of the insulator is 385±5 mm; the outer diameter of the upper umbrella is 400±5 mm, the outer diameter of the middle umbrella is 350±2 mm, and the outer diameter of the lower umbrella is 300±5 mm; the axial distance between the upper and middle umbrellas is 55~65 mm, the axial distance between the middle and lower umbrellas is 45~55 mm, the thickness of each umbrella skirt is 10~14 mm, and the radius of the umbrella root rounded corner is 8~12 mm; the nominal creepage distance of the insulator is set to 700±10 mm, 1000±10 mm, or 1350±10 mm according to the anti-pollution level, and the glaze layer thickness is 0.30~0.55 mm.
[0013] Preferably, the double-layer sacrificial zinc ring anti-corrosion assembly includes an upper zinc ring and a lower zinc ring arranged adjacent to each other along the axial direction of the steel foot. The radial thickness of the upper zinc ring and the lower zinc ring is 3~5 mm, and the axial distance between them is 5~10 mm. The axial width of the upper zinc ring is 14~18 mm, and the axial width of the lower zinc ring is 10~14 mm. The inner wall of the cast steel cap is provided with a zinc-aluminum composite anti-corrosion layer with a thickness of 80 μm~140 μm.
[0014] Preferably, the firing temperature of the high-alumina porcelain insulation body is 1300℃~1320℃, and the heating rate is 15~22℃ / h; the modified cement adhesive layer is formed by segmented constant temperature curing at 40℃ and 60℃; the high-alumina porcelain insulation body is screened piece by piece under water pressure of 36 MPa before gluing, and the insulators after gluing are subjected to 500,000 cycles of alternating tensile fatigue sampling inspection according to the production batch.
[0015] A second aspect of the present invention provides a method for preparing the 840 kN high-tonnage disc suspension porcelain insulator, comprising the following steps: The raw materials are weighed according to the raw material ratio of the high-alumina ceramic insulation body and water is added to make slurry. The slurry is ball-milled, sand-milled to refine and remove iron. The slurry is dehydrated, aged and vacuum-kneaded to obtain clay segments. A blank with a hollow cylindrical head and a gradient three-umbrella skirt is formed and the blank is air-dried in stages in a vertical state. The blank is glazed and an anti-slip sand layer is formed on the glued surface of the cylindrical head. The ceramic parts are fired using a segmented temperature control system. Each fired ceramic part is screened by internal water pressure at 36 MPa. The qualified ceramic parts are coaxially glued with cast steel caps and spherical bearing steel feet and cured at segmented constant temperature of 40℃ and 60℃. A double-layer sacrificial zinc ring anti-corrosion component is installed on the steel feet. The product is inspected for appearance, dimensions and electromechanical performance, and 500,000 cycles of alternating tensile fatigue sampling inspection are carried out according to the production batch.
[0016] Preferably, the solid content of the pulp after pulping is 58%~62%, the ball milling time is 6~10 h, and the sand milling time is 20~24 h; the particle size D of the pulp after sand milling is... 90 ≤5 μm; the moisture content of the sludge after pressure filtration is 19%~22%, the aging time is 20~28 h, and the vacuum degree of vacuum sludge refining is -0.09~-0.085 MPa.
[0017] Preferably, the molding pressure is 20 MPa to 30 MPa; the staged air drying includes air drying at 20℃ to 25℃ and relative humidity of 75% to 85% for 24 to 36 hours, air drying at 28℃ to 35℃ and relative humidity of 60% to 70% for 36 to 60 hours, and drying at 38℃ to 45℃ and relative humidity of 45% to 55% for 12 to 24 hours, so that the residual moisture content of the green body is ≤1.2%.
[0018] Preferably, during the firing of the billet, the heating rate is 40℃ / h to 55℃ / h for 20℃ to 600℃, 20℃ / h to 30℃ / h for 600℃ to 1100℃, and 15℃ / h to 22℃ / h for 1100℃ to 1300℃, and the billet is held at 1300℃ to 1320℃ for 2 to 4 hours; after holding, the cooling rate to 900℃ is 30℃ / h to 45℃ / h, and the cooling rate to 900℃ to 400℃ is 40℃ / h to 60℃ / h, and the billet is cooled with the furnace after the temperature drops below 400℃.
[0019] Preferably, the thickness of the modified cement adhesive layer during the gluing process is 8-15 mm; after gluing, it is first pre-cured at 20℃-25℃ and relative humidity not less than 90% for 10-14 h, then heated to 40℃ at a heating rate of ≤5℃ / h and kept at that temperature for 24 h, then heated to 60℃ and kept at that temperature for 48 h, and finally cooled to room temperature at a cooling rate of ≤5℃ / h.
[0020] Preferably, the pressure increase rate of the water pressure screening within 36 MPa is 0.5~1.5 MPa / s, and the pressure holding time is 60~120s; ceramic parts that show leakage, abnormal pressure drop, visible cracks, or abnormal acoustic emission are judged as unqualified.
[0021] Preferably, the 500,000-cycle alternating tensile fatigue sampling test uses a sinusoidal load with a lower limit of 252~336kN, an upper limit of 504~588kN, and a frequency of 1.5~2.5 Hz. At least 3 insulators are sampled from each production batch for testing. After completing the cycle, the samples show no visible cracks and no debonding at the adhesive interface.
[0022] The third aspect of this invention provides the application of the 840 kN high-tonnage disc suspension porcelain insulator in ultra-high voltage overhead transmission lines, the method of which is as follows: Multiple 840 kN high-tonnage disc suspension porcelain insulators are connected in series to form a tension insulator string, which is used for mechanical bearing and electrical insulation between conductors and towers of 1000 kV UHV AC lines, ±800 kV UHV DC lines, or ±1100 kV UHV DC lines.
[0023] Preferably, the tension insulator string is used for tension towers with large elevation differences across rivers and valleys, in areas with heavy ice cover, strong wind areas, coastal areas with heavy salt spray and pollution, or long-distance transmission lines of new energy bases.
[0024] Preferably, the tension insulator string is used to connect 8×1250 mm 2 Or 10×1520 mm 2 Large cross-section multi-split conductor.
[0025] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention employs a double-arc gradually thickened cylindrical head, which, in conjunction with a steel cap arc stress buffer groove, a steel foot spherical bearing structure, and a modified cement adhesive layer, forms a relatively gentle load transfer path. This can disperse the local stress at the ceramic head and the adhesive interface, reduce the risk of ceramic cracking and adhesive layer debonding, and improve the mechanical reliability of the insulator under long-term alternating loads.
[0026] This invention uses high-purity α-alumina ceramic material, and improves the density and mechanical strength of the ceramic body through sand milling, vacuum mixing, pressure molding, staged air drying, and segmented firing, while reducing drying cracks, firing deformation, and performance dispersion in thick-walled ceramic parts. A modified cementitious adhesive containing water-reducing agents, artificial ceramic sand aggregate, and defoamers, combined with segmented constant-temperature curing, reduces adhesive layer porosity and curing shrinkage, improving the bonding strength and resistance to thermal cycling at the adhesive interface.
[0027] This invention adopts a gradient three-umbrella structure with gradually decreasing outer diameter, which is beneficial to increase the effective creepage distance, reduce dirt accumulation and water film bridging; by setting a double-layer sacrificial zinc ring and a steel cap anti-corrosion layer, it can delay the local depletion of the zinc layer and improve the corrosion resistance of the steel foot in DC, salt spray and polluted environments.
[0028] This invention also employs a 36 MPa internal water pressure method to screen for internal defects in each ceramic component, and evaluates the long-term load-bearing reliability of the finished product through 500,000 cycles of alternating tensile fatigue sampling inspection, thereby improving the product's factory quality and batch consistency. Test results show that this invention can reduce stress concentration at the head, improve electromechanical failure load, fatigue life, flashover performance, and batch pass rate, demonstrating promising engineering application prospects. Attached Figure Description
[0029] The present invention will be further described below with reference to the accompanying drawings.
[0030] Figure 1 This is a schematic flowchart of the preparation method of the present invention; Figure 2 This is a photograph of the semi-finished high-alumina ceramic insulating body of the present invention. Detailed Implementation
[0031] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0032] Raw materials, parameters, and testing methods: Unless otherwise stated, the ceramic aggregate proportions in this invention are expressed in parts by weight, with high-alumina silicate cement measured in 100 parts, and polycarboxylate superplasticizer, artificial ceramic sand aggregate, and organic defoamer all measured relative to the cement mass. Particle size D 90 The particle size distribution was determined using a laser particle size analyzer. The radius of curvature, adhesive layer thickness, and coaxiality were determined using coordinate measuring machine (CMM) or industrial computed tomography (CT).
[0033] The finite element analysis employed a three-dimensional solid model consisting of a cast steel cap, a high-alumina ceramic insulating body, a modified cement adhesive layer, and steel feet. The model was fixed at the connection end of the steel cap, and an axial tensile load of 840 kN was applied to the lower end of the steel feet. The mesh size at the critical arc and the adhesive layer end was ≤1 mm. The stress concentration factor was defined as the ratio of the maximum first principal tensile stress at the cylindrical head to the nominal tensile stress at the same cross-section.
[0034] For the electromechanical failure load test, 12 specimens were used in each group, and the failure load, average value, standard deviation, and minimum value of each specimen were recorded. For the fatigue test, 3 specimens were used in each group, with a lower load limit of 252 kN, an upper load limit of 504 kN, a frequency of 2 Hz, and 500,000 cycles. For the thermal cycling test, 5 specimens were used in each group, held at -40℃ for 2 hours, then switched to 70℃ for 2 hours, constituting one cycle. For the artificial contamination test, 5 short-stranded plates were used in each group, and the 50% flashover voltage was compared under the same equivalent salt density, ash density, polarity, and voltage boosting method. The salt spray electrolytic corrosion test used a 5% sodium chloride solution, 35℃, and DC voltage conditions, with a test duration of 1000 hours.
[0035] Example 1 This embodiment describes the preparation of an 840 kN high-tonnage disc suspension porcelain insulator suitable for 1000 kV UHV AC lines.
[0036] The dry-basis raw materials of the high-alumina porcelain insulation body include, by weight, 93 parts of α-high-purity alumina powder with a purity of 99.5%, 4 parts of low-sodium quartz powder, 2.4 parts of low-potassium sodium feldspar, and 0.6 parts of composite mineralizer. The composite mineralizer is composed of magnesium oxide and barium carbonate in a mass ratio of 3:2. The raw materials are mixed with water to prepare a slurry with a solid content of 60%, ball-milled for 8 hours, sand-milled for 24 hours, and iron is removed to reduce the slurry particle size D. 90 It is 4.8 μm.
[0037] The slurry was filtered to a moisture content of 21%, aged for 24 hours, and then vacuum-kneaded at -0.09 MPa. A blank with a cylindrical head and a gradient three-umbrella skirt was obtained using a molding pressure of 25 MPa. The cylindrical head has a height of 105 mm, an outer diameter of 125 mm, a sidewall thickness of 23 mm, a top thickness of 22 mm, and a hollow hole diameter of 79 mm. The first outer arc radius is 26 mm, the second outer arc radius is 10 mm, the first inner arc radius is 12 mm, and the second inner arc radius is 7.5 mm.
[0038] The outer diameter of the upper umbrella of the gradient three-canopy umbrella is 400 mm, the outer diameter of the middle umbrella is 350 mm, and the outer diameter of the lower umbrella is 300 mm. The axial distance between the upper and middle umbrellas is 60 mm, the axial distance between the middle and lower umbrellas is 50 mm, the thickness of each umbrella skirt is 12 mm, the radius of the umbrella root corner is 10 mm, the self-cleaning angle of the umbrella surface is 12°, the nominal creepage distance is 700 mm, and the structural height is 385 mm.
[0039] The green body was air-dried vertically at 23℃ and 80% relative humidity for 30 h, then air-dried at 32℃ and 65% relative humidity for 48 h, and finally dried at 42℃ and 50% relative humidity for 18 h, so that the residual moisture content of the green body was 1.0%.
[0040] The body is glazed, and the anti-slip area at the cylindrical head is treated with corundum porcelain sand with a particle size of 0.60~1.00 mm for glazing. After firing, the glaze layer thickness is 0.45 mm, and the height of the sand particles protruding from the glaze surface is 0.6 mm.
[0041] During firing, the temperature is increased at 50℃ / h from 20℃ to 600℃, at 25℃ / h from 600℃ to 1100℃, and at 18℃ / h from 1100℃ to 1310℃, and held at 1310℃ for 3 hours. Then, it is cooled to 900℃ at 35℃ / h, and then cooled to 400℃ at 50℃ / h. After the temperature drops below 400℃, it is cooled with the furnace.
[0042] Each fired ceramic piece was subjected to a 36 MPa internal water pressure screening process, with a pressure increase rate of 1 MPa / s and a holding time of 90 s. Qualified ceramic pieces were coaxially glued to cast steel caps and feet. The radius of the arc-shaped stress buffer groove on the inner wall of the steel cap was 8 mm and the depth was 3 mm; the radius of the spherical bearing structure at the top of the steel foot was 40 mm and the height of the spherical crown was 10 mm; the radial thickness of the adhesive layer on the side of the steel cap was 10 mm, and the axial thickness of the adhesive layer at the top of the spherical surface on the side of the steel foot was 12 mm.
[0043] The modified cement binder, based on 100 parts by weight of high-alumina silicate cement (aluminate content of 42%), contains 0.8 parts of polycarboxylate superplasticizer, 1.2 parts of artificial ceramic sand aggregate with a particle size of 0.20~0.50 mm, and 0.5 parts of organic defoamer, with a water-cement ratio of 0.30. After binding, it is pre-cured at 23℃ and 95% relative humidity for 12 hours, then heated to 40℃ at a rate of 5℃ / h and held for 24 hours, then heated to 60℃ and held for 48 hours, and finally cooled to room temperature at a rate of 4℃ / h.
[0044] An upper zinc ring and a lower zinc ring are installed in the middle of the steel foot. The upper zinc ring has an axial width of 16 mm and a radial thickness of 4 mm, while the lower zinc ring has an axial width of 12 mm and a radial thickness of 4 mm. The axial distance between the two is 8 mm. The zinc-aluminum composite anti-corrosion layer on the inner wall of the steel cap is 110 μm thick.
[0045] The electromechanical failure load test result of the product in this embodiment is 862 kN. No visible cracks appeared after 500,000 cycles of alternating fatigue. The AC artificial flashover voltage is 246 kV. The single batch product qualification rate is 97.5%. It is compatible with 1000 kV AC 8×1250mm 2 Conductor tension string.
[0046] Example 2 The difference from Example 1 is that this example is used for ±1100 kV UHVDC heavy-load cross-river lines; the nominal creepage distance is 1000 mm, the axial width of the upper zinc ring is 18 mm and the radial thickness is 5 mm, the axial width of the lower zinc ring is 14 mm and the radial thickness is 5 mm, and the thickness of the zinc-aluminum composite anti-corrosion layer on the inner wall of the steel cap is 130 μm; the remaining raw materials, structure and preparation steps are the same as in Example 1.
[0047] The DC artificial flashover voltage in this embodiment is 172 kV, and no visible cracks are found at the adhesive interface after 1000 cycles of hot and cold cycling from -40℃ to 70℃.
[0048] Example 3 The difference from Example 1 is that: this example is used for ±800 kV UHVDC mountain icing lines in wind and solar bases; the thickness of the lower umbrella root is 14 mm, and the axial distance between the middle umbrella and the lower umbrella is 55 mm; the heating rate in the 1100℃~1305℃ range is 16℃ / h, and it is kept at 1305℃ for 3.5 h; the nominal creepage distance is 1000 mm; the remaining raw materials, structure and preparation steps are the same as in Example 1.
[0049] In this embodiment, all ceramic parts were individually screened under a water pressure of 36 MPa, and no visible cracks were found at the head after the ice overload test.
[0050] Example 4 The difference from Example 1 is that the dry base raw materials of the high-alumina ceramic insulation body include 92 parts by weight of α-high-purity alumina powder, 5 parts of low-sodium quartz powder, 2.5 parts of low-potassium sodium feldspar and 0.5 parts of composite mineralizer; the maximum firing temperature is 1300℃ and the holding time is 4 h; the remaining structure and preparation steps are the same as in Example 1.
[0051] Example 5 The difference from Example 1 is that the dry base raw materials of the high-alumina ceramic insulation body include 95 parts by weight of α-high-purity alumina powder, 3 parts of low-sodium quartz powder, 1.5 parts of low-potassium sodium feldspar and 0.5 parts of composite mineralizer; the maximum firing temperature is 1320℃ and the holding time is 2 h; the remaining structure and preparation steps are the same as in Example 1.
[0052] Example 6 The difference from Example 2 is that this example is used for ±1100 kV UHVDC heavy-load transmission lines in heavily polluted coastal areas with salt spray; the nominal creepage distance is 1350 mm. Under the condition that the outer diameter of the upper umbrella is 400 mm, the outer diameter of the middle umbrella is 350 mm, the outer diameter of the lower umbrella is 300 mm, and the insulator structure height is 385 mm, the nominal creepage distance of the insulator along the outer surface of the porcelain body is made to reach 1350 mm by adjusting the umbrella surface curves and the lower edge contour of the upper, middle, and lower umbrellas; the remaining raw materials, structures, and preparation steps are the same as in Example 2.
[0053] Comparative Example 1 The difference from Example 1 is that the cylindrical head uses only a single circular arc transition, the inner wall of the steel cap does not have a circular arc stress buffer groove, and the top of the steel foot uses a planar pressure-bearing structure; the other raw materials, dimensions and preparation steps are the same as in Example 1.
[0054] Comparative Example 2 The difference from Example 1 is that the adhesive used is high aluminosilicate cement without added polycarboxylate superplasticizer, artificial ceramic sand aggregate and organic defoamer, with a water-cement ratio of 0.38, and after gluing, it is naturally cured at 25°C for 72 h; the rest of the structure, raw materials and preparation steps are the same as in Example 1.
[0055] Comparative Example 3 The difference from Example 2 is that a double umbrella structure with an upper umbrella outer diameter of 400 mm and a lower umbrella outer diameter of 350 mm is adopted, and only one sacrificial zinc ring with an axial width of 18 mm and a radial thickness of 5 mm is set on the steel foot; the rest of the structure, raw materials and preparation steps are the same as in Example 2.
[0056] Comparative Example 4 The difference from Example 1 is that the fired ceramic parts are not subjected to individual screening under water pressure of 36 MPa, and the finished products are not subjected to 500,000 cycles of alternating fatigue sampling inspection. Only the appearance, dimensions and specified tensile load are inspected. The remaining structure, raw materials and preparation steps are the same as in Example 1.
[0057] Finite element analysis was performed on Example 1 and Comparative Example 1 respectively. Under an axial load of 840 kN, the stress concentration factor corresponding to the maximum first principal tensile stress at the cylindrical head of Example 1 was 1.58, while that of Comparative Example 1 was 2.21. The high-stress region of Example 1 was circumferentially dispersed along the double-circular arc transition zone, while the high-stress region of Comparative Example 1 was concentrated at the end of the single-circular arc and the end of the adhesive layer.
[0058] Twelve specimens from both Example 1 and Comparative Example 1 were subjected to electromechanical failure load tests. The average electromechanical failure load test result for Example 1 was 862 kN, with a minimum of 849 kN; the average electromechanical failure load test result for Comparative Example 1 was 836 kN, with a minimum of 807 kN. All three fatigue specimens from Example 1 completed 500,000 cycles without visible cracks; the three specimens from Comparative Example 1 developed adhesive seams or microcracks at the cylindrical head after 228,000, 241,000, and 263,000 cycles, respectively. This demonstrates that the combination of the double-arc gradually thickened cylindrical head, the steel cap arc stress buffer groove, and the steel foot spherical bearing structure can reduce local stress concentration at the cylindrical head and adhesive interface, and improve the load-bearing stability and alternating fatigue performance under a high load of 840 kN.
[0059] Five samples each from Example 1 and Comparative Example 2 were subjected to thermal cycling tests. In Example 1, no visible cracks appeared at the interface after 1000 cycles; in Comparative Example 2, the adhesive layer debonded at the ends during the 598th to 662nd cycles. In Comparative Example 2, three fatigue samples developed adhesive interface cracks at 312,000, 338,000, and 356,000 cycles, respectively. This demonstrates that the modified cement adhesive, incorporating polycarboxylate superplasticizer, artificial ceramic aggregate, and organic defoamer, combined with a segmented constant-temperature curing process, effectively reduces internal defects and curing shrinkage in the adhesive layer, thereby improving the thermal cycling resistance and alternating load tolerance of the bonded interface.
[0060] Example 2 and Comparative Example 3 were each composed of 5 short strings for DC artificial pollution testing. The 50% flashover voltage of Example 2 was 172 kV, and that of Comparative Example 3 was 145 kV. After 1000 h of salt spray electrolytic corrosion, the total mass loss of the double-layer sacrificial zinc ring in Example 2 was 2.6 g, and no continuous red rust appeared on the steel foot substrate; the mass loss of the single zinc ring in Comparative Example 3 was 7.4 g, and red rust appeared on the steel foot at the location where the zinc layer was depleted. This demonstrates that the gradient three-umbrella skirt and double-layer sacrificial zinc ring anti-corrosion assembly can respectively improve the external insulation performance and the electrolytic corrosion resistance of the steel foot under polluted conditions.
[0061] Five short strings of samples from Examples 6 and 2 were assembled respectively, and DC artificial pollution tests were conducted under the same equivalent salt density, ash density, DC polarity, environmental conditions, and voltage boosting method. The nominal creepage distance of Example 2 was 1000 mm, and the 50% flashover voltage was 172 kV; the nominal creepage distance of Example 6 was 1350 mm, and the 50% flashover voltage was 198 kV. The 50% flashover voltage of Example 6 was approximately 15.1% higher than that of Example 2. After 1000 cycles of thermal cycling from -40℃ to 70℃, no visible cracks appeared at the adhesive interface of Example 6. All three fatigue samples completed 500,000 alternating tensile cycles without any visible cracks or debonding at the adhesive interface.
[0062] Therefore, it can be seen that, while keeping the insulator structure height and the basic outer diameters of the upper, middle, and lower umbrellas unchanged, increasing the nominal creepage distance from 1000 mm to 1350 mm by adjusting the umbrella surface curve and the lower edge profile of the gradient three-umbrella skirts can further improve the surface flashover withstand capability under DC heavy pollution conditions. Simultaneously, this creepage distance adjustment does not significantly weaken the thermal cycling stability of the adhesive interface or the alternating mechanical fatigue performance of the insulator. Therefore, Example 6 is more suitable for UHVDC heavy-load transmission lines in coastal salt spray, high humidity, and heavy pollution environments.
[0063] In Example 1, 400 units were continuously prepared. Six units were rejected during the 36 MPa water pressure screening, and another 5 were rejected during the binding and final inspection stages. 389 units passed the first inspection, resulting in a single-batch pass rate of 97.25%. The average pass rate for three consecutive batches was 97.2%. The pass rate for another batch of products described in Example 1 was 97.5%. In Comparative Example 4, 400 units were continuously prepared. During the final inspection and subsequent destructive testing, 53 units were deemed unqualified, resulting in a pass rate of 86.8%. Therefore, by using 36 MPa water pressure screening before binding and alternating tensile fatigue sampling inspection in the finished product stage, products with internal defects or insufficient binding reliability can be identified in advance, improving the quality consistency of batch products.
[0064] A performance and engineering application comparison was conducted between a traditional 420 kN insulator, an existing 550 kN insulator, and the 840 kN high-tonnage disc suspension porcelain insulator of this invention. The results show that the rated mechanical failure load of the insulator of this invention reaches 840 kN, the stress concentration factor at the head is reduced to 1.58, it withstands 500,000 alternating fatigue cycles without cracking, and the flexural strength of the porcelain component reaches 288 MPa. In Example 2, with a nominal creepage distance of 1000 mm, the 50% flashover voltage in a DC artificial pollution test is 172 kV, while in Example 6, with a nominal creepage distance of 1350 mm, it is further increased to 198 kV. After 1000 cycles of hot and cold cycling, no cracking occurred at the adhesive interface, and the average batch pass rate reached 97.2%. Therefore, this invention can select different nominal creepage distances according to the pollution level of the line, maintaining high mechanical load-bearing capacity and fatigue resistance while also meeting the external insulation requirements under different pollution environments.
[0065] Under the condition of meeting the same line load requirements, the total number of insulators per tower can be reduced from about 3,500 pieces for traditional 420 kN products or about 2,680 pieces for 550 kN products to about 1,000 pieces. The steel consumption of the tower can be reduced to about 78%. This shows that while improving load-bearing reliability, fatigue resistance and electrical performance, the present invention can reduce the number of insulators and matching hardware, and reduce the tower load and the amount of engineering materials used.
[0066] The insulator in Example 1 is used for 1000 kV AC 8×1250 mm 2 Tension insulator strings are used in several applications: Example 2 is for ±1100kV DC heavy-load cross-river lines; Example 3 is for ±800kV DC mountain icing lines; and Example 6 is for ±1100kV UHVDC heavy-load transmission lines in heavily polluted coastal areas with salt spray. Multiple insulators are connected in series to form tension insulator strings, based on the requirements of line mechanical load, insulation coordination, pollution level, and safety factor.
[0067] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A high-tonnage disc-type suspension porcelain insulator with a capacity of 840 kN, characterized in that, It includes a high-alumina ceramic insulating body, a cast steel cap, a steel foot, and a modified cement adhesive layer for adhesively connecting the high-alumina ceramic insulating body to the cast steel cap and the steel foot respectively. The high-alumina ceramic insulating body includes a cylindrical head and a gradient three-umbrella skirt located below the cylindrical head. The cylindrical head is a hollow cylindrical head. The outer and inner sides of the cylindrical head are formed by two tangent and connected arcs to form a double arc gradual wall thickness transition structure. The cylindrical side wall thickness of the cylindrical head is 23 mm, the top thickness is 22 mm, and the glued surface of the cylindrical head is provided with an anti-slip sand layer with a height of 0.6 mm. The inner wall of the cast steel cap is provided with an arc-shaped stress buffer groove. The top of the steel foot is a spherical pressure-bearing structure, which is matched with the inner double arc transition structure of the cylindrical head through the modified cement adhesive layer. The steel foot is fitted with a double-layer sacrificial zinc ring anti-corrosion assembly in the middle. The outer diameters of the upper, middle, and lower umbrellas of the gradient three-umbrella skirt decrease progressively from top to bottom, and the self-cleaning tilt angle of the umbrella surface is 12°.
2. The 840 kN high-tonnage disc-shaped suspension porcelain insulator according to claim 1, characterized in that, The cylindrical head has a height of 105±4 mm and an outer diameter of 125±4 mm. The diameter of the hollow hole in the cylindrical head is 79±5 mm. The outer double arc includes a first outer arc and a second outer arc that are tangentially connected. The radius of the first outer arc is 24~28 mm, and the radius of the second outer arc is 8~12 mm. The inner double arc includes a first inner arc and a second inner arc that are tangentially connected. The radius of the first inner arc is 10~14 mm, and the radius of the second inner arc is 6~9 mm.
3. The 840 kN high-tonnage disc-type suspension porcelain insulator according to claim 1, characterized in that, The arc radius of the circular stress buffer groove is 6~10 mm and the radial depth is 2~4 mm; the spherical bearing structure has a spherical radius of 35~45 mm and a spherical crown height of 8~12 mm; the radial thickness of the modified cement adhesive layer on one side of the cast steel cap is 8~12 mm, and the axial thickness of the modified cement adhesive layer on the top of the spherical surface on the side of the steel foot is 10~15 mm; the coaxiality deviation of the cast steel cap, the high-alumina ceramic insulating body and the steel foot is ≤0.8 mm.
4. The 840 kN high-tonnage disc-shaped suspension porcelain insulator according to claim 1, characterized in that, The dry-based raw materials of the high-alumina ceramic insulation body, by weight, include: 92-95 parts α-high-purity alumina powder, 3-5 parts low-sodium quartz powder, 1.5-2.5 parts low-potassium sodium feldspar, and 0.3-0.8 parts composite mineralizer; the purity of the α-high-purity alumina powder is not less than 99.5%, and the particle size D of the raw material after sand milling is... 90 ≤5 μm; the composite mineralizer is composed of magnesium oxide and barium carbonate in a mass ratio of 1:1 to 2:
1.
5. The 840 kN high-tonnage disc-type suspension porcelain insulator according to claim 1, characterized in that, The modified cementitious binder, based on 100 parts by weight of high-alumina silicate cement, comprises 0.8 parts of polycarboxylate superplasticizer, 1.2 parts of artificial ceramic sand aggregate, and 0.5 parts of organic defoamer, with a water-cement ratio of 0.28~0.
32. The particle size of the artificial ceramic sand aggregate is 0.15~0.60 mm. The aluminate content of the high-alumina silicate cement is 35-50%.
6. The 840 kN high-tonnage disc-shaped suspension porcelain insulator according to claim 1, characterized in that, The insulator has a structural height of 385±5 mm; the outer diameter of the upper shed is 400±5 mm, the outer diameter of the middle shed is 350±2 mm, and the outer diameter of the lower shed is 300±5 mm; the axial distance between the upper and middle sheds is 55~65 mm, the axial distance between the middle and lower sheds is 45~55 mm, the thickness of each shed skirt is 10~14 mm, and the radius of the shed root rounded corner is 8~12 mm; the nominal creepage distance of the insulator is set to 700±10 mm, 1000±10 mm, or 1350±10 mm according to the anti-pollution level, and the glaze layer thickness is 0.30~0.55 mm.
7. The 840 kN high-tonnage disc-type suspension porcelain insulator according to claim 1, characterized in that, The double-layer sacrificial zinc ring anti-corrosion assembly includes an upper zinc ring and a lower zinc ring arranged adjacent to each other along the axial direction of the steel foot. The radial thickness of the upper zinc ring and the lower zinc ring is 3~5 mm, and the axial distance between them is 5~10 mm. The axial width of the upper zinc ring is 14~18 mm, and the axial width of the lower zinc ring is 10~14 mm. The inner wall of the cast steel cap is provided with a zinc-aluminum composite anti-corrosion layer with a thickness of 80 μm~140 μm.
8. The 840 kN high-tonnage disc-type suspension porcelain insulator according to claim 1, characterized in that, The high-alumina ceramic insulation body is fired at a temperature of 1300℃~1320℃, with a heating rate of 15~22℃ / h; the modified cement adhesive layer is formed by segmented constant temperature curing at 40℃ and 60℃.
9. The method for preparing the 840 kN high-tonnage disc suspension porcelain insulator according to any one of claims 1 to 8, characterized in that, Includes the following steps: Weigh the raw materials according to the raw material ratio and add water to make a slurry. The slurry is then refined by ball milling and sand milling, and iron is removed. The slurry is then dehydrated, aged, and vacuum-kneaded to obtain clay segments. The clay segments are then shaped to obtain a blank with a hollow cylindrical head and a gradient three-umbrella skirt, and the blank is air-dried in stages in a vertical position. The blank is then glazed, and an anti-slip sand layer is formed on the glued surface of the cylindrical head. The ceramic pieces are then fired using a segmented temperature control system. Each fired ceramic piece is screened under 36 MPa internal water pressure; qualified ceramic pieces are coaxially glued with cast steel caps and spherical bearing steel feet, and cured in sections at 40℃ and 60℃; double-layer sacrificial zinc ring anti-corrosion components are installed on the steel feet; the products are inspected for appearance, dimensions, and electromechanical performance, and 500,000 cycles of alternating tensile fatigue are sampled for each production batch.
10. The application of the 840 kN high-tonnage disc suspension porcelain insulator according to any one of claims 1 to 7 in ultra-high voltage overhead transmission lines, characterized in that, Multiple 840 kN high-tonnage disc suspension porcelain insulators are connected in series to form a tension insulator string, which is used for mechanical bearing and electrical insulation between conductors and towers of 1000 kV UHV AC lines, ±800 kV UHV DC lines or ±1100 kV UHV DC lines. The tension insulator strings are used for tension towers with large elevation differences across rivers and valleys, in areas with heavy ice cover, strong winds, coastal areas with heavy salt spray and pollution, or long-distance transmission lines from new energy bases. The tension insulator strings are used to connect 8×1250 mm... 2 Or 10×1520 mm 2 Large cross-section multi-split conductor.
Citation Information
Patent Citations
Disc-shaped suspension-type porcelain insulator
CN104992794A
High-strength aging-resistant porcelain insulator and preparation method thereof
CN110845224A
Three-umbrella type disc-shaped suspension insulator
CN113113193A